Internationalization and the Degradation of Jepara Carving Traditions in the Beginning of 21st Century - Indrahti, Sri; Yuliati, Dewi; Alamsyah, Alamsyah (Indonesian Historical Studies, 2024)
This article examines the process of degradation in Jepara’s ornamental woodcarving, driven primarily by internationalization. In this context, degradation refers to the decline or deterioration of the traditional Jepara woodcarving motifs as a result of modernization. Using historical methodology, the study reconstructs the factors that have contributed to the decline of Jepara’s ornamental woodcarving. The degradation process began with the arrival of foreign investors. On one hand, these investors facilitated the global marketing of Jepara carvings. However, this also required Jepara’s woodcarving products to conform to international market tastes, leading to a shift towards minimalist or even plain designs without traditional carvings. The changing consumer preferences gradually displaced the distinctive Jepara motifs, which were perceived as outdated, less appealing, and less competitive compared to foreign products. This decline in quality was further exacerbated by the export boom at the end of the 20th century. The findings reveal that the degradation of Jepara's ornamental motifs has significantly impacted the lives of local artisans, both in terms of the diminishing value and quality of their work, and in their struggle for survival by adapting to market demands